The Interaction of Entrepreneurship and Institutions - Magnus Henrekson; Tino Sanandaji (Research Institute of Industrial Economics (IFN), 2010)
Previous research, notably Baumol (1990), has highlighted the role of insti-tutions in channeling entrepreneurial supply into productive, unproductive or destructive activities. However, entrepreneurship is not only influenced by institutionsentrepreneurs often help shape institutions themselves. The bilateral causal relation between entrepreneurs and institutions is examined in this paper. Entrepreneurs affect institutions in at least three ways. Entrepreneurship abiding by existing institutions is occasionally disruptive enough to challenge the foundations of prevailing institutions. Entrepreneurs sometimes have the opportunity to evade institutions, which tends to undermine the effectiveness of the institutions, or cause institutions to change for the better. Lastly, entrepreneurs can directly alter institutions through innovative political entrepreneurship. As business entrepreneurship, innovative political activity may be productive or unproductive, depending on the incentives facing entrepreneurs.
Keywords: L50; M13; O31; P14; 330; Entrepreneurship; Innovation; Institutions; Regulation; Self-employment; Entrepreneurship-Ansatz; Selbstständige; Industriepolitik; Technischer Fortschritt; Institutionalismus